Development of a multi-year pediatric antibiogram in Georgia identifies antibiotic resistance changes over the past ten years - Matthew Linam; Madeleine Goldstein; Tracy Huang; Adrianna Westbrook; Robert C. Jerris; Mark D. Gonzalez (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract